An exploration of barriers and facilitators to implementing a nonalcoholic fatty liver disease pathway for people with type 2 diabetes in primary care. Issue 6 (7th February 2022) - Gracen, Lucy; Hayward, Kelly L.; Aikebuse, Melanie; Williams, Suzanne; Russell, Anthony; O'Beirne, James; Powell, Elizabeth E.; Valery, Patricia C.
Abstract: Aims: We explored barriers and facilitators to the implementation of nonalcoholic fatty liver disease (NAFLD) pathway for people with diabetes to identify determinants of behaviour surrounding the diagnosis, assessment and management of NAFLD. Methods: Health practitioners ( n = 24) recruited from multidisciplinary diabetes clinics in primary care ( n = 3) and hospital ( n = 1) settings participated in four focus group discussions, and common themes were identified using thematic analysis. Results: Lack of knowledge and access to resources were key factors that underpinned an inconsistent approach by clinicians to NAFLD diagnosis and risk stratification and impacted their confidence to discuss the diagnosis with patients. Participants often prioritised other medical issues above NAFLD due to lack of concern about liver‐related consequences, reluctance to overburden patients with information, lack of time and perceived absence of accessible fibrosis tests. All participants agreed that implementation of a NAFLD pathway would improve patient care and the general practitioners proposed that screening for NAFLD could be incorporated into routine review cycles for type 2 diabetes. A consistent message from participants was that educating patients about their liver disease needs to be implemented in an integrated care pathway. Conclusions: From the perspectives of health practitioners, there is a gap in clinical practice for the implementation of clear, evidence‐based guidelines for NAFLD in people with T2D. By focusing on comorbidity prevention and integrating NAFLD as a diabetes complication to be addressed during established cycles of care, many barriers to implementing a NAFLD pathway in primary care could be overcome.